Awareness and Perceptions of Food Safety Risks and Risk Management in Poultry Production and Slaughter: A Qualitative Study of Direct-Market Poultry Producers in Maryland - Baron, Patrick; Frattaroli, Shannon (PLOS ONE, 2016)
The objective of this study was to document and understand the perceptions and opinions of small-scale poultry producers who market directly to consumers about microbial food safety risks in the poultry supply chain. Between January and November 2014, we conducted semi-structured, in-depth interviews with a convenience sample of 16 owner-operators of Maryland direct-market commercial poultry farms. Three overarching thematic categories emerged from these interviews that describe: 1) characteristics of Maryland direct-market poultry production and processing; 2) microbial food safety risk awareness and risk management in small-scale poultry production, slaughter and processing; and 3) motivations for prioritizing food safety in the statewide direct-market poultry supply chain. Key informants provided valuable insights on many topics relevant to evaluating microbial food safety in the Maryland direct-market poultry supply chain, including: direct-market poultry production and processing practices and models, perspectives on issues related to food safety risk management, perspectives on direct-market agriculture economics and marketing strategies, and ideas for how to enhance food safety at the direct-market level of the Maryland poultry supply chain. The findings have policy implications and provide insights into food safety in small-scale commercial poultry production, processing, distribution and retail. In addition, the findings will inform future food safety research on the small-scale US poultry supply chain.